Designed electron-deficient gold nanoparticles for a room-temperature Csp3–Csp3 coupling reaction. Issue 6 (21st December 2020) - Yu, Qiu-Ying; Su, Hui; Zhai, Guang-Yao; Zhang, Shi-Nan; Sun, Lu-Han; Chen, Jie-Sheng; Li, Xin-Hao
Abstract : Room-temperature autocleavage of C–Br bonds via electron-deficient Au nanoparticles formed as a result of the rectifying contact with boron-doped carbons. Abstract : Stille cross-coupling reactions catalysed by an ideal catalyst combining the high activity of homogeneous catalysts and the reusability of heterogeneous catalysts are of great interest for C–C bond formation, which is a widely used reaction in fine chemistry. Despite great effort to increase the utilization ratio of surface metal atoms, the activity of heterogeneous catalysts under mild conditions remains unsatisfactory. Herein, we design a proof-of-concept strategy to trigger the room-temperature activity of heterogeneous Au catalysts by decreasing the electron density at the interface of a rationally designed Schottky heterojunction of Au metals and boron-doped carbons. The electron-deficient Au nanoparticles formed as a result of the rectifying contact with boron-doped carbons facilitate the autocleavage of C–Br bonds for highly efficient C–C coupling reactions of alkylbromides and allylstannanes with a TOF value of 5199 h −1 at room temperature, surpassing that of the state-of-the-art homogeneous catalyst.